Exploring the Strong Interaction of Three-Body Systems at the LHC - Acharya, S.; Adamova, D.; Rinella, G. Aglieri; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S. U.; Ahuja, I.; Akindinov, A.; Al-Turany, M.; Aleksandrov, D.; et al. (AMER PHYSICAL SOC, 2024)
Deuterons are atomic nuclei composed of a neutron and a proton held together by the strong interaction. Unbound ensembles composed of a deuteron and a third nucleon have been investigated in the past using scattering experiments, and they constitute a fundamental reference in nuclear physics to constrain nuclear interactions and the properties of nuclei. In this work, Kthorn-d and p-d femtoscopic correlations measured by the ALICE Collaboration in proton-proton (pp) collisions at root s = 13 TeV at the Large Hadron Collider (LHC) are presented. It is demonstrated that correlations in momentum space between deuterons and kaons or protons allow us to study three-hadron systems at distances comparable with the proton radius. The analysis of the Kthorn-d correlation shows that the relative distances at which deuterons and protons or kaons are produced are around 2 fm. The analysis of the p-d correlation shows that only a full three-body calculation that accounts for the internal structure of the deuteron can explain the data. In particular, the sensitivity of the observable to the short-range part of the interaction is demonstrated. These results indicate that correlations involving light nuclei in pp collisions at the LHC will also provide access to any threebody system in the strange and charm sectors.
Keywords: PHASE-SHIFT ANALYSIS; FINAL-STATE INTERACTIONS; PD ELASTIC-SCATTERING; CROSS-SECTIONS; LIGHT-NUCLEI; COLLISIONS; PARTICLES; FEMTOSCOPY; AU-197; FORCES; Physics